Optimization of the learning process of quadruple jumps in figure skating - Knoll, Ka. (World Congress of Performance Analysis of Sport VIII, 2008)
Our detailed individual biomechanical orientations and their realizations in the training of triple-triple jump combinations have been proved as good preparations for the quadruple jump for one skater (P3). The skater P2 has learned the technique of landing jump combinations also, with the transfer to a landed triple Axel. Skater P1 has not reached the aim in the quadruple Jump, but he has presented perfect triple-triple combination jumps in the competition. The regular controls and corrections supported the whole learning process and provided an effective individual feedback. The skater has reduced his time of learning the quadruple Toe Loop to one season. In addition the quality of triple jump combinations has been significantly improved.